Borrelia persica infection in dogs and cats: clinical manifestations, clinicopathological findings and genetic characterization. Issue 1 (December 2016) - Baneth, Gad; Nachum-Biala, Yaarit; Halperin, Tamar; Hershko, Yizhak; Kleinerman, Gabriela; Anug, Yigal; Abdeen, Ziad; Lavy, Eran; Aroch, Itamar; Straubinger, Reinhard
Abstract Background Relapsing fever (RF) is an acute infectious disease caused by arthropod-borne spirochetes of the genusBorrelia . The disease is characterized by recurrent episodes of fever that concur with spirochetemia. The RF borrelioses include louse-borne RF caused byBorrelia recurrentis and tick-borne endemic RF transmitted by argasid soft ticks and caused by severalBorrelia spp. such asB. crocidurae, B. coriaceae, B. duttoni, B. hermsii, B. hispanica andB. persica . Human infection withB. persica is transmitted by the soft tickOrnithodoros tholozani and has been reported from Iran, Israel, Egypt, India, and Central Asia. Methods During 2003–2015, five cats and five dogs from northern, central and southern Israel were presented for veterinary care and detected with borrelia spirochetemia by blood smear microscopy. The causative infective agent in these animals was identified and characterized by PCR from blood and sequencing of parts of the flagellin (flab ), 16S rRNA and glycerophosphodiester phosphodiestrase (GlpQ ) genes. Results All animals were infected withB. persica genetically identical to the causative agent of human RF. Phylogenetic analysis indicated that DNA sequences from these pet carnivores clustered together withB. persica genotypes I and II from humans andO. tholozani ticks and distinctly from other RFBorrelia spp. The main clinical findings in cats included lethargy, anorexia, anemia in 5/5 cats and thrombocytopenia in 4/5. All dogs were lethargic and anorectic, 4/5 were febrile and anemic and 3/5 were thrombocytopenic. Three dogs were co-infected withBabesia spp. The animals were all treated with antibiotics and the survival rate of both dogs and cats was 80 %. The cat and dog that succumbed to disease died one day after the initiation of antibiotic treatment, while survival in the others was followed by the rapid disappearance of spirochetemia. Conclusions This is the first report of disease due toB. persica infection in cats and the first case series in dogs. Infection was associated with anemia and thrombocytopenia. Fever was more frequently observed in dogs than cats. Domestic canines and felines suffer from clinical disease due toB. persica infection and may also serve as sentinels for human infection.